“Extending TPB Framework: Investigating Environmental and Social Influences on Sustainable Investment Intention” (Journal of Informatics Education and Research, 2024)
Purpose: The present study has attempted to extend the TPB Framework evaluating factors influencing behavioural intention towards Sustainable investments by adding Environmental concern (EC) and Social Responsibility (SR) in the current model.Methodology: Data has been collected from 425 investors and Structural equation model (SEM) technique has been used for the current Sustainable investment intentions.Findings: The study reveals significant positive impact of ATT, SN, EC, SR and PBC on Sustainable investment intentions.Practical Implications: Investment companies can leverage insights from this study to design and promote tailored ESG investment products that resonate with environmentally and socially conscious investors. The government can use these insights to develop policies that promote sustainable investments, encouraging responsible financial practices.Originality: The study sought to address a critical Gap in the research literature by examining collective impact of EC and SR on the TPB constructs.